A Study on Knowledge and Use of Emergency Contraceptive Pills among Female Sex Workers of Ahmedabad - Rachna Kapoor; Mayank Patel; Himanshu Nayak (Medsci Publications, 2018)
Background: Female Sex Workers (FSWs) are at high risk for unin- tended pregnancy. One of the key interventions to reduce unin- tended pregnancy and unsafe abortion is availability of emergency contraception. The present study was conducted to assess the knowledge ,attitude and practices regarding ECPs among FSWs of Ahmedabad as well as the hazards of overusing it. Methods: A cross sectional community based study was carried out among 1023 FSWs in Ahmedabad during February 2014 to June 2014. FSWs were interviewed by systematic random sam- pling using a standard pre designed and pretested semi- struc- tured proforma. Results: Overall, 45.3% of the FSWs had ever heard of ECPs when asked directly and all of them mentioned ECPs by name sponta- neously. Knowledge of ECP was independently associated with age, education, marital status, type of family and the socioeconom- ic status of the FSWs. Only 15.6% of FSWs had ever used ECPs. Conclusion: The study pointed out the need for increasing the knowledge of FSWs about emergency contraception pills as well as making them aware about the hazards of overusing it.